2014
DOI: 10.1073/pnas.1407393111
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 is required for shaping the magnitude, affinity distribution, and memory of T cells responding to subunit immunization

Abstract: An elusive goal of cellular immune vaccines is the generation of large numbers of antigen-specific T cells in response to subunit immunization. A broad spectrum of cytokines and cell-surface costimulatory molecules are known to shape the programming, magnitude, and repertoire of T cells responding to vaccination. We show here that the majority of innate immune receptor agonistbased vaccine adjuvants unexpectedly depend on IL-27 for eliciting CD4 + and CD8 + T-cell responses. This is in sharp contrast to infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 59 publications
(72 reference statements)
3
83
1
Order By: Relevance
“…One possibility may be through Program Death-1/Program Death Ligand 1 (PD-1/PD-L1) signaling, because populations of T cells deficient in PD-1 expand more and have higher-avidity TCRs (Jiang et al, 2016). Another factor may be levels of interleukin (IL) 27, a cytokine that is produced by APCs and has been shown to play a role in the generation of high-avidity T cells (Pennock et al, 2014). Similarly, IL-12 produced by dendritic cells may also contribute to the generation of these cells (DeBenedette et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility may be through Program Death-1/Program Death Ligand 1 (PD-1/PD-L1) signaling, because populations of T cells deficient in PD-1 expand more and have higher-avidity TCRs (Jiang et al, 2016). Another factor may be levels of interleukin (IL) 27, a cytokine that is produced by APCs and has been shown to play a role in the generation of high-avidity T cells (Pennock et al, 2014). Similarly, IL-12 produced by dendritic cells may also contribute to the generation of these cells (DeBenedette et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are models in which even outside the competitive setting, IL-27 is required for optimal CD8 + T cell responses (60). A major advance in this area has been the finding that the ability of vaccines that include an adjuvant composed of agonistic anti-CD40 antibodies combined with TLR ligands to elicit CD4 + and CD8 + T cell responses depends on the ability of IL-27 to promote T cell survival (116). These studies are notable because in parallel experiments the authors have shown that IL-27 limits infection-induced CD8 + T cell responses.…”
Section: Il-27 Promotes T Cell Responsesmentioning
confidence: 99%
“…To date, there are only a few subunit vaccine platforms capable of producing this level of T cell expansion, one of which is a combination adjuvant stimulating both an innate receptor (such as a TLR) and CD40 (combined innate/CD40). Much like the B cell response, the use of either of these single adjuvants typically produces around 10–50,000 total antigen specific CD8+ T cells [2], a number that is non-protective with respect to T cell responses [13]. In contrast, after a single exposure, the combined innate/CD40 adjuvant can produce a similar number of antigen specific T cells (~1–3 million antigen specific T cells), and in the same time frame (7 days), as the infectious challenge [2, 10, 13, 44, 45].…”
Section: T Cell Vs B Cell Fauna… All About the Numbersmentioning
confidence: 99%
“…Much like the B cell response, the use of either of these single adjuvants typically produces around 10–50,000 total antigen specific CD8+ T cells [2], a number that is non-protective with respect to T cell responses [13]. In contrast, after a single exposure, the combined innate/CD40 adjuvant can produce a similar number of antigen specific T cells (~1–3 million antigen specific T cells), and in the same time frame (7 days), as the infectious challenge [2, 10, 13, 44, 45]. As a result of the potency of this vaccine adjuvant, we and others [4648] have spent years studying its underlying mechanisms in mice and have recently shown its capacity to produce robust CD8 and CD4 responses in non-human primates [49].…”
Section: T Cell Vs B Cell Fauna… All About the Numbersmentioning
confidence: 99%
See 1 more Smart Citation